La France : Les difficultés d’une réussite - Coulomb, Pierre; Delorme, Hélène (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
Since 1970 the government brings differrenciated pressure to bear on production prices but this policy goes with the emergence of France as a big world food exporter. However since 1974 the instability of external trade and the sensible drop in agricultural income has led, 20 years after the i960's laws, to a new agricultural policy. Despite the large current debates, the definition of this new policy seems to have to await the post-crisis phase.